2002
DOI: 10.1667/0033-7587(2002)158[0475:rotfct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Thyroid Follicular Cells to Gamma Irradiation Compared to Proton Irradiation: II. The Role of Connexin 32

Abstract: The objective of this study was to determine whether connexin 32-type gap junctions contribute to the "contact effect" in follicular thyrocytes and whether the response is influenced by radiation quality. Our previous studies demonstrated that early-passage follicular cultures of Fischer rat thyroid cells express functional connexin 32 gap junctions, with later-passage cultures expressing a truncated nonfunctional form of the protein. This model allowed us to assess the role of connexin 32 in radiation respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Other experiments have revealed that early-passage cultures of rat thyroid cells, which express functional Cx32 channels, are more resistant to ␥ irradiation than later-passage cultures, which express a truncated, nonfunctional form of Cx32. Strikingly, this beneficial effect was not observed after proton irradiation (181). These observations may be related to those made on insulin-producing ␤-cells after exposure to drugs that experimentally reproduce the massive cell death observed in pancreatic islets at the onset of type I diabetes (5,265).…”
Section: Connexins and Hormone Actionmentioning
confidence: 77%
See 1 more Smart Citation
“…Other experiments have revealed that early-passage cultures of rat thyroid cells, which express functional Cx32 channels, are more resistant to ␥ irradiation than later-passage cultures, which express a truncated, nonfunctional form of Cx32. Strikingly, this beneficial effect was not observed after proton irradiation (181). These observations may be related to those made on insulin-producing ␤-cells after exposure to drugs that experimentally reproduce the massive cell death observed in pancreatic islets at the onset of type I diabetes (5,265).…”
Section: Connexins and Hormone Actionmentioning
confidence: 77%
“…Cx32 and coupling are lost with passages in culture, together with the ability of the cells to form follicular structures (166,180,181,364,365). These alterations can be reverted by exposing cell monolayers to thyroid stimulating hormone (TSH) (365) or by transfection of communication-incompetent thyrocytes with Cx32, but not Cx43 (545).…”
Section: Glycoprotein-producing Endocrinesmentioning
confidence: 99%
“…55 In another report on the effects of proton irradiation, activation of apoptosis in thyroid follicular cells was investigated by searching for different markers such as cytoplasmic DNA fragments and micronuclei. 56 These authors also reported a block of cell cycle at the G2 phase but didn't describe modifications of the mRNA phenotype nor the increase of ROS induced by proton irradiation. 56 It is interesting to note that also gamma irradiation of CCRF-CEM, a human lymphoblastic leukemia cell line, has been reported to induce arrest at the G2/M phase of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical in vivo studies on proton therapy are usually performed using young animals (2, 4). Since proton therapy is utilized for tumor treatment of children (due to the superior targeting advantages over gamma radiation) as well as middle-age to older patients (40, 41), it is important to investigate the efficacy of such therapy, along with the radiobiology of protons in general, as a function of host age, gender and genetics. We have demonstrated proton-induced tumor signaling to be modulated with age and found suppression of TGFβ to play a key role in inhibiting tumor growth in proton-irradiated old mice.…”
Section: Discussionmentioning
confidence: 99%